Influence of ceria distribution on the redox behaviour of nanoparticulated CeO2‐SiO2 systems with application in catalysis1. (20th May 2014) - Cabeza, I.; Souto, L. G.; Pintado, J. M.; Pereira, C.; Freire, C.; Blanco, G.; Abel, Marie‐Laure; Rossi, Antonella; Watts, John F.
<x xml:space="preserve">Abstract</x> Ceria has been broadly employed in many technological applications. However, because of geo‐strategic concerns, reducing the lanthanide loadings in heterogeneous catalysts while maintaining their good properties has become a main goal in many recent studies. In this work, ceria has been dispersed over two different silica nanoparticle supports, with different sizes and porosity, producing samples with different ceria crystal size and distribution. The influence of these parameters on the redox behaviour of the resulting samples has been investigated, finding a correlation between ceria distribution and both the reducibility and the resistance to deactivation of the systems. Samples obtained from porous silica, consisting of small ceria nanocrystals uniformly distributed along the pore structure of silica, exhibited better reducibility, whereas samples prepared from non‐porous silica, presenting a core‐shell like structure, had a better resistance against thermal deactivation. Copyright © 2014 John Wiley & Sons, Ltd.